Combining cervical cancer screening for mothers with schoolgirl vaccination during human papillomavirus (HPV) vaccine implementation in South Africa: results from the VACCS1 and VACCS2 trials. Issue 5 (25th January 2022) - Dreyer, Greta; Botha, Matthys H; Snyman, Leon C; Visser, Cathy; Burden, Riekie; Laubscher, Nicolene; Grond, Bertha; Richter, Karin; Becker, Piet J; Harvey, Justin; van der Merwe, Frederick H
Abstract : Objective: The platform provided by human papillomavirus (HPV) vaccination for linked public health interventions to improve cervical cancer prevention remains incompletely explored. The Vaccine And Cervical Cancer Screen (VACCS) cross-sectional observation trials aimed to evaluate the efficacy of school-based HPV vaccination linked with maternal cervical cancer screening. Methods: Girls from 29 schools in two provinces in South Africa were invited in writing to receive HPV vaccination. Two approaches to informed consent were compared, namely an audiovisual presentation (VACCS1) and in written format (VACCS2). Markers of vaccine uptake and coverage were calculated, namely uptake among the invited and consented cohorts, and rates of completion and sufficient vaccination. Mothers and female guardians received educational material about cervical cancer, and either a self-sampling device or an invitation to attend existing screening facilities. Knowledge was assessed via structured questionnaires (before and after), and screening uptake was self-reported and directly assessed and compared between these approaches. Results: Vaccine acceptance among 5137 invited girls was similar for the two methods of consent; 99.3% of consented girls received a first dose; overall completion rate was 90.5%. More girls were vaccinated using a two-dose (974/1016 (95.9%)) than a three-dose regimen (1859/2030 (91.6%)). The questionnaire (n=906) showed poor maternal knowledge which improved significantly (p<0.05) after health education; only 54% of mothers reported any previous screening. The offer of a self-sampling device (n=2247) was accepted by 43.9% of mothers, but only 26% of those invited to screen at existing facilities (n=396) reported subsequent screening. Conclusions: Successful linking of primary health interventions to control cervical cancer was demonstrated. School-based HPV vaccination, linked to health education, self-sampling, and molecular screening resulted in significant improvements in knowledge and screening.